Social Innovation for Community Well-Being: Evaluating Grassroots Interventions in Addressing Local Development Challenges - Emily R Sophie; Amelia M Hayes (Zabags International Journal of Engagement, 2026)
This article examines the implementation of community-based social innovation as a strategic approach to addressing local development challenges that cannot be fully resolved through formal policies or market mechanisms. The study aims to analyze the effectiveness of grassroots interventions in enhancing community well-being and to identify the supporting and inhibiting factors that influence program success. Employing a qualitative case study design within a constructivist paradigm, data were collected through in-depth interviews, participatory observation, focus group discussions, and analysis of organizational and policy documents. The findings reveal that the success of community-based social innovation is strongly shaped by community participation, adaptive local leadership, multi-stakeholder collaborative networks, institutional support, sustainable funding, and organizational capacity to adapt to social dynamics. Barriers identified include limited participation in certain areas, conflicting stakeholder interests, restricted access to technology, and weak monitoring and evaluation mechanisms. The theoretical contribution of this study lies in the integration of social innovation, community development, participatory development, social capital, and collaborative governance frameworks to understand the dynamics of local development. Practically, the study highlights the need to strengthen community capacity, ensure consistent institutional support, and develop sustainable funding strategies so that community-based social innovation can serve as a cornerstone of inclusive and sustainable local development.